MENINGKATKAN HASIL BELAJAR DENGAN MENGGUNAKAN MEDIA MONTESSORI PADA MATA PELAJARAN MATEMATIKA KELAS 1 SD N 067259 MEDAN JOHOR: Penelitian Tindakan Kelas - Vina Adelia Sinaga; Rumiris Lumban Gaol (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This Classroom Action Research (CAR) aimed to improve the learning outcomes of first-grade students at SD N 067259 Medan Johor in Mathematics, specifically on the topic of plane shapes, through the use of Montessori media. This research was motivated by initial observations indicating variations in students' understanding and suboptimal learning outcomes in plane shapes. The action hypothesis in this study was that the use of concrete and manipulative Montessori media could enhance student engagement and understanding of plane shape concepts, thereby positively impacting their learning outcomes. This research was conducted in two cycles, each involving the stages of planning, action, observation, and reflection. The subjects of the study were first-grade students at SD N 067259 Medan Johor for the academic year 2024/2025. Research data were collected through observations of student and teacher activities during the learning process and formative tests at the end of each cycle. Data analysis was performed quantitatively (comparison of average scores and the percentage of students achieving the learning mastery criteria between cycles) and qualitatively (description of learning activities and reflections). The results of the study showed a significant increase in student learning outcomes from Cycle I to Cycle II after the implementation of learning using Montessori media. The class average score increased from 70 to 85, and the percentage of students achieving the Minimum Completeness Criteria (KKM) increased from 50% to 90%. The conclusion of this research is that the use of Montessori media is effective in improving the learning outcomes of first-grade students at SD N 067259 Medan Johor in the topic of plane shapes. This research provides practical implications for first-grade teachers in implementing more concrete and student-centered learning approaches through the use of Montessori media to enhance the understanding of mathematical concepts